Effect of 1-Butyl-3-Methylimidazolium Tricyanomethane in Extractive Desulphurization Process on Model Oil - Syamsul Bahari, Abdullah; Mohd Amirul Mukmin, Abdullah; Z., Man (Universiti Malaysia Pahang, 2019)
Driven by regulatory requirements to reduce the content of sulphur in fuels, the demand to find an alternative process to hydrodesulphurization is on the rise. In this study, experiments were conducted for the removal of sulphur compound (present as benzothiophene or BT) with concentration of 2000 ppm in the model oil (present as n-dodecane or n-C12) using 1-butyl-3-methylimidazolium tricyanomethane ([bmim][TCM]) as the extractant. The effects of stirring speed, extraction time and water content on the extraction efficiency were investigated. In the end, the loading factor of the [bmim][TCM] is also discussed where it can be concluded that, more than one mole of [bmim][TCM] may interacted with one mole of BT during extractive desulphurization process.